2011
DOI: 10.1111/j.1464-0597.2011.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing Range in an Electric Vehicle: Understanding Psychological Barriers

Abstract: Range of electric vehicles (EVs) has long been considered a major barrier in acceptance of electric mobility. We examined the nature of how range is experienced in an EV and whether variables from other adaptation contexts, notably stress, have explanatory power for inter‐individual differences in what we term comfortable range. Forty EVs were leased to a sample of users for a 6‐month field study. Qualitative and quantitative analyses of range experiences were performed, including regression analyses to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
198
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(206 citation statements)
references
References 37 publications
4
198
1
3
Order By: Relevance
“…Many research efforts are ongoing to improve both problems of which the first one will be more deeply discussed in Section 3. In literature [9][10][11][12][13][14][15] the range anxiety is identified as mainly a psychological barrier since most people drive less kilometers a day than the range of current EVs. This problem is enhanced by the long charging time of an EV as well as the lack of abundantly available charging stations for electric vehicles.…”
Section: State Of the Art-hevmentioning
confidence: 99%
“…Many research efforts are ongoing to improve both problems of which the first one will be more deeply discussed in Section 3. In literature [9][10][11][12][13][14][15] the range anxiety is identified as mainly a psychological barrier since most people drive less kilometers a day than the range of current EVs. This problem is enhanced by the long charging time of an EV as well as the lack of abundantly available charging stations for electric vehicles.…”
Section: State Of the Art-hevmentioning
confidence: 99%
“…The specific notion of "range anxiety" has emerged to reflect the problem of EV drivers developing negative psychological feelings of anxiousness when they consider whether they will be able to properly recharge their vehicle on a longer trip (Pasogluu et al 2015;Franke and Krems 2013a;Frank and Krems 2013b;Franke et al 2012;Neubauer et al 2014). Indeed, some research has indicated that the notion of battery range and range anxiety is the single most important factor in whether a user will consider driving or purchasing an EV (Egbue and Long 2012;Duigou et al 2014).…”
Section: Sociomaterials Commensurabilitymentioning
confidence: 99%
“…For the realization of EVs, many studies have looked at the potential impact, adoption limitation, potential operational pattern and actual usage simulation of EVs in current electricity grids [17][18][19][20]. Most research indicates that energy replenishment is a significant factor in making EVs more competitive because of range anxiety among the EV users [4,5].…”
Section: Related Workmentioning
confidence: 99%
“…The abovementioned reasons make it probable that EV users will be forced to stop and wait, which results in waiting anxiety. In addition, EV users trade-off between the remaining battery energy, the location distribution of charging facilities and their travel plans, which easily results in range anxiety [4,5]. Therefore, more researchers and EV operators are turning their attention to battery swapping [6][7][8].…”
Section: Introductionmentioning
confidence: 99%